Polarization on the Polemic of the Job Creation Law - Sulistya Ningrum (Journal of Contemporary Sociological Issues, 2023)
The Omnibus Law on the Job Creation Law (UU Cipta Kerja) which was authorized in October 2020 amid the COVID-19 outbreak has raised pros and cons among the public, policymakers, investors, and workers in Indonesia. It is considered to be detrimental to the lower middle class while benefiting certain entities. Consequently, there was a polarization of public discourse in cyberspace. Therefore, this study aimed to map polarization trends in the internet community regarding the polemic on the Job Creation Law. This research used mixed methods with the Corpus-Assisted Discourse Study (CADS) framework. The trend amongst the cyber community indicated that there was group polarization in perceiving these issues, where both pro and con groups have different arguments and justifications in addressing the matter. The research data was in the form of tweets corpus totaling 12,224 tokens related to the Job Creation Law. The Natural Language Toolkit (NLTK) package built into Python 3.9.2 was used for tokenization and stopword removal. Lancsbox 6.0 was used to compute keywords and determine concordances. Furthermore, the significance of the keyword frequency was calculated using the Log-Likelihood test. This study identified three main topics in the controversial debate on the Job Creation Law, namely 1) State financial and economic policies; 2) Employment, length of service, and income; and 3) Environment and sustainability. Keywords: Corpus-Assisted Discourse Study (CADS), Cyberspace, Job Creation Law, Omnibus Law, Polarization.